Práticas psicológicas na atenção e proteção básicas de saúde e assistência social. - Ferreira, Alexsandra Marcela Lins de Souza (2018)
Psychological practice in Brazil has undergone several transformations since the regulation of Psychology as a profession. From the 1980s, the work of the psychologist, who was previously mainly in the private clinic, moves to the public sector due to the increasing demand on psychology professionals in public health and health care policies. However, the psychological practices still do not seem to satisfactorily contemplate the political and social aspects that the present time demands, considering the strong presence of these components in the psychological suffering. In this perspective, this dissertation aims at the field of basic health care and basic social protection of social assistance. It takes as a field-theme the experience of being a psychologist in these contexts, whose specificities and singularities call us special attention. In order to support the study, we conducted a qualitative research in this field, in which we interviewed four (4) psychologists, two (02) of whom work in public health policies and 02 (two) in Social Assistance. We adopted the cartographic management interview and the logbook as compasses to get us closer to the intended field-theme. The understanding of the narratives was carried out from the point of view of the cartographic method. The comprehensive possibilities that have been highlighted in this study point to an important moment of tension and reflection about training for working in public policies. Special emphasis has been given to the hostile working conditions to which the psychologists of these fields are immersed.